PEMETAAN KUALIFIKASI: PEMENUHAN KEBUTUHAN STAKEHOLDER DALAM REKRUTMEN PUSTAKAWAN - Yunita, Rahmi; Karunia, Leila; Akbar, Fikri (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2023)
This article explores the mapping of qualifications in librarian recruitment in Indonesia. The objectives of mapping qualifications in librarian recruitment in Indonesia: (1) determine the level of librarian qualifications based on education level; (2) reviewing the qualification standards for diploma level librarians in Indonesia; (3) reviewing the qualification standards for librarians at undergraduate education level in Indonesia. This research method was carried out through three strategic stages, namely (1) data collection (2) data analysis; and (presentation of the results of data analysis (reporting). Data collection was carried out using the indexation method through recruitment data for librarians for state and private institutions in Indonesia for the last three years. Research data analysis was carried out descriptively quantitative and qualitative. The research results showed variations in the needs of Library Science graduates between CPNS and CPPPK recruitment, with diploma III level being more dominant in CPPPK, while strata 1 is more dominant in CPNS; in private agencies, job opportunities vary reflecting the complexity of job demands, emphasizing the importance of understanding and mapping qualifications in building a strong foundation for growth, innovation and sustainability in the library sector, providing guidance for prospective students and stakeholders.